ANALISIS PROSES PEMBELAJARAN MENGGUNAKAN SEMPOA PADA ANAK USIA 5-6 TAHUN DI BIMBINGAN BELAJAR SEMPOA SIP KOTA PEKANBARU - Rahim, Wilasma; Chairlsyah, Daviq; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to learn the overview of the learning process using the abacus in children aged 5-6 years at the guidance of Abacus SIP Kota Pekanbaru. In the educational institution one of the school children aged 5-6 children only learned about the basics of numbers through concepts. Unlike in the guidance of learning Abacus SIP, in this study guidance researchers found the fact that the phenomenon of children aged 5-6 years is able to use the abacus to help the learning process exceeds the set by Permendikbud 137 and the learning process is different from the way children are taught to be faster in counting only by using Abacus. The subject of this study is the head of foundations, teachers, parents and 7 children. The method used in this research is a qualitatively descriptive method, which is a method directed to describe or expose the outcome of the research. The collection of the research data uses three main techniques: interviews, observations and documentation studies. Data analysis techniques using three kinds of qualitative data analysis activities are data reduction, Data Model and withdrawal/vertification conclusion. From the results of the study, it is known that the use of an inaction in the learning process signifies the effectiveness of improving counting ability, as well as the Abacus method can improve the ability of other disciplines. This method of learning with the use of the abacus can encourage children to be more active, creative and innovative.Â Key Words : Abacus, Learing, Tutoring